Penerapan Strategi PDCA untuk Meningkatkan Produktivitas Kerja melalui Penguatan Kerja Sama Tim dan Komunikasi Organisasi - Eka Nurul Azizah; Anita Kartika Sari; Tri Wahjoedi; Agung Dwi Nugroho; Sofyan Lazuardi (CV. Multi Kreasi Media, 2024)
−The activity of community service in this program will try to provide support to increase work productivity at CV. BKM Sidoarjo through the implementation of strategies based on PDCA (Plan-Do-Check-Act). Emphasis is placed on strengthening teamwork and organizational communication to break down big obstacles: a lack of trust between team members, a limitation in the competence of new employees, and an inability to be open with any conflict. The different stages of the process involve problem identification through planning, intense provisioning with simulation and role-playing methods during the 'Do' stage, periodic evaluation in the 'Check' stage, and corrective steps for sustainability in the 'Action' stage. Implementation results indicated a productivity increase of 41% over and above the initial target. This program has succeeded in bringing about a culture of collaboration and efficiency in work. The suggestions for sustainability: to create a continuous provisioning program, besides using the 5-S concept as work environment efficiency support. With such benefits being accrued to them in the process, the case would serve as an invaluable reference for other similar organizations grappling with such obstacles.